Crohn's Disease and Ulcerative Colitis From Epidemiology and Immunobiology to a Rational Diagnostic and Therapeutic Approach - Baumgart, Daniel C.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The conditions of Crohn’s disease and ulcerative colitis are excellent examples of  how the exponential growth of knowledge in biomedical science can make a remarkable impact on clinical practice and patient’s quality of life. It has led to the development of unique novel immunomodulatory treatments. These are continuously being refined to treat not only the two original conditions in the gut, but the systemic immunologic illness with its associated extraintestinal disorders. New therapies are sometimes complex and associated with important risks requiring a deeper understanding of their molecular principles from clinicians.   Crohn’s Disease and Ulcerative Colitis serves as a unique combined resource for physicians and scientists addressing the needs of both groups. It will stimulate exchange and collaboration and shorten the path between discovery and application of new knowledge and also help clinicians understand new therapeutic concepts from their origins. This volume provides an introduction to mucosal immunology which forms the basis of modern immunotherapy. It also serves as a comprehensive guide to the current diagnostic modalities, including enhanced imaging techniques such as MRI and CT enterography, virtual colonoscopy, ultrasound, and endomicroscopy as well as conventional and complex immunomodulatory principles. Each chapter is written by experts in their field and includes the most up to date information. Crohn’s Disease and Ulcerative Colitis will be of great value to gastroenterologists, surgeons, internists, pediatricians and gynecologists trainees, as well as all those involved in Crohn’s disease, ulcerative colitis and related autoimmune disorders.
The genetics of inflammatory bowel disease -- Environmental factors in the epidemiology of inflammatory bowel disease.-The intestinal immune system in health -- Understanding the epithelial barrier in inflammatory bowel disease.- Intestinal microbiology and ecology  in inflammatory bowel disease.- Microbial recognition and pathogen-associated molecular pattern (PAMP) receptors  in inflammatory bowel disease -- Inflammasomes  in inflammatory bowel disease.-Antimicrobial peptides  in inflammatory bowel disease -- Vascular responses to intestinal inflammation  in inflammatory bowel disease -- Immunobiology of dendritic cells in inflammatory bowel disease.-Immunobiology of T-Cells in inflammatory bowel disease -- Immunobiology of B-Cells in inflammatory bowel disease.-Immunobiology of monocytes and macrophages in inflammatory bowel disease -- Immunobiology of epithelial cells in inflammatory bowel disease -- The Th1, Th2 and Th17 paradigm in inflammatory bowel disease -- Preclinical studies using mouse models of inflammatory bowel disease.- Enhanced endoscopy in inflammatory bowel disease -- MRI in Inflammatory Bowel Disease -- CT in inflammatory bowel disease.-Ultrasound in inflammatory bowel disease.-Laboratory evaluation including novel diagnostic markers  of inflammatory bowel disease -- Histology and pathology of inflammatory bowel disease -- Activity indices based assessment of disease activity in inflammatory bowel disease.- Endoscopic assessment of disease activity and mucosal healing in inflammatory bowel disease.-Evaluation of quality of life in inflammatory bowel disease -- The natural history of inflammatory bowel disease -- Conventional medical management of Crohn’s disease: sulfasalazine -- Conventional medical management of Crohn’s disease: corticosteroids.-Conventional medical management of Crohn’s disease: azathioprine and 6-mercaptopurine.- Conventional medical management of Crohn’s Disease: Methotrexate.-Biologic Treatment of Crohn’s Disease: Adalimumab -- Biologic Treatment of Crohn’s Disease: Certolizumab -- Biologic Therapy of Crohn's disease: Infliximab.- Biologic Treatment of Crohn’s Disease: briakinumab and ustekinumab.-Biologic Treatment of Crohn’s Disease: natalizumab, vedolizumab and edrolizumab (rHUMab beta 7).-Conventional medical management of ulcerative colitis: sulfasalazine and 5-aminosalicylates.-Conventional medical management of ulcerative colitis: corticosteroids -- Conventional medical management of ulcerative colitis: azathioprinetherapy: Azathioprine.-  Conventional medical management of ulcerative colitis: cyclosporine -- Conventional medical management of ulcerative colitis: tacrolimus.- Biologic therapy of ulcerative colitis: infliximab and adalimumab -- Biologic therapy of ulcerative colitis: natalizumab, vedolizumab, edrolizumab (rHUMab beta 7) -- Probiotics, prebiotics, and antibiotics in medical management inflammatory bowel disease -- Step-Up vs. Top-Down Approach in medical management of inflammatory bowel disease -- Surgical management of Crohn's disease and ulcerative colitis -- Extraintestinal manifestations of inflammatory bowel disease: autoimmune hepatitis.-Extraintestinal manifestations of inflammatory bowel disease: primary sclerosing cholangitis (PSC) -- Extraintestinal manifestations of inflammatory bowel disease: autoimmune pancreatitis and other IgG4-related conditions.- Extraintestinal manifestations of inflammatory bowel disease: cutaneous and oral manifestations of inflammatory bowel disease -- Extraintestinal manifestations of inflammatory bowel disease:  arthritis, arthropathy and osteoporosis -- Nutrition in inflammatory bowel disease.-Fertility and pregnancy in inflammatory bowel disease -- Pediatric aspects in inflammatory bowel disease -- Management and prevention of infectious diseases in inflammatory bowel disease patients.-Diagnosis and management of colorectal neoplasia in patients with inflammatory bowel disease -- How to identify high risk patients in inflammatory bowel disease?.- Patient perspective on inflammatory bowel disease -- Patient resources in inflammatory bowel disease.
Keywords: Gastroenterology .; Gastroenterology